Corporate governance practices as a reflection of the institutions, economics and political environment in Sub-Saharan Africa Anglophone countries. (2016) - Afolabi, Adeoye Amuda; Sy, Aida
This paper reviews the historical background of corporate governance, emerging issues in the development and practice of corporate governance in Ghana, Nigeria and South Africa. It compared the corporate governance institutions, politics, corruption and economics of each country. We find that in Ghana there are lacks of institutional shareholders, while in Nigeria and South Africa there are institutional shareholders. However, shareholders association in Ghana and South Africa are not active compared with that of Nigeria. In addition, South Africa have a stronger institutional framework than Ghana and Nigeria, this really provide an evidence to show that corporate governance practices in South Africa seems to be better than Ghana and Nigeria. Generally, we find that corruption and bribery, politics, economics influence effective corporate governance practice in each country. We recommend that the socio-political and economic culture in Sub-Saharan Africa Anglophone in particular Nigeria and Ghana requires need for urgent re-orientation in order to restructure the National Institutions of each of the country. As a result, corporate governance guideline should be tailor towards the political economic and cultural environment of those countries.